Temperature Controlled Sequential Gelation in Composite Microgel Suspensions. (24th March 2015) - Appel, Jeroen; de Lange, Niek; van der Kooij, Hanne M.; van de Laar, Ties; ten Hove, Jan Bart; Kodger, Thomas E.; Sprakel, Joris
<x xml:space="preserve">Abstract</x> Depending on the volume fraction and interparticle interactions, colloidal suspensions can exhibit a variety of physical states, ranging from fluids, crystals, and glasses to gels. For microgel particles made of thermoresponsive polymers, both parameters can be tuned using environmental parameters such as temperature and ionic strength, making them excellent systems to experimentally study state transitions in colloidal suspensions. Using a simple two‐step synthesis it is shown that the properties of composite microgels, with a fluorescent latex core and a responsive microgel shell, can be finely tuned. With this system the transitions between glass, liquid, and gel states for suspensions composed of a single species are explored. Finally, a suspension of two species of microgels is demonstrated, with different transition temperatures, gels in a sequential manner. Upon increasing temperature a distinct core–sheath structure is formed with a primary gel composed of the species with lowest transition temperature, which acts as a scaffold for the aggregation of the second species.